Comparative Proteomic Analysis of Spike-Development Inhibited and Normal Tillers of Wheat 3558 - Yong-sheng ZHENG; Xiao-gang MA; De-zhao CHI; Ai-nong GAO; Li-hui LI; Wei-hua LIU (Journal of Integrative Agriculture, 2013)
Spike number is one of three yield-related factors and is closely related to wheat yield. In the present study, we found that the inhibited and normal tillers of the 3558 line presented phenotypic differences at the elongation stage by morphological and anatomical analysis. We then initiated a proteomic study using two-dimensional electrophoresis (2-DE) and nanoscale liquid chromatography-high-definition tandem mass spectroscopy, to isolate and identify the key proteins and metabolic pathways related to spike-development inhibition. A total of 31 differentially expressed proteins (DEPs), which were mainly involved in cell cycle regulation, photosynthesis, glycolysis, stress response, and oxidation-reduction reactions, were isolated and identified. 14-3-3-like proteins and proliferating cell nuclear antigen (PCNA), involved in cell-cycle regulation, were dramatically down-regulated in inhibited tillers compared to normal tillers. Six spots corresponding to degraded Rubisco large subunits, involved in photosynthesis, were detected in different locations of the 2-DE gels and were up-regulated in inhibited tillers. In addition, the relative levels of DEPs involved in glycolysis and oxidation-reduction reactions changed dramatically. Development was blocked or delayed at the elongation stage in the inhibited tillers of 3558. Weakened energy metabolism might be one reason that the inhibited tillers could not joint and develop into spikes. These DEPs and related metabolic pathways are significant for understanding the mechanism of spike-development inhibition and studying the spike-development process in wheat.